Composite film, photoelectric device, preparation method of photoelectric device and display device
By setting the acid-resistant modification layer of alkaline carbon nanomaterial on one side of the functional layer of the functional film and setting the electronic barrier layer of low-priced metal oxide material on the other side, the corrosion problem caused by the difference in material properties of the functional film is solved, and the corrosion problem caused by the functional film is achieved. The stability and performance improvement of the functional layer.
Patent Information
- Application Number
- CN202311157349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-02-18
AI Technical Summary
Functional films are corrosion due to differences in material properties in the preparation of multi-layer materials, which affects stability of performance.
An acid-resistant modification layer is provided on one side of the functional layer, an alkaline carbon nanomaterial is used, and an electron barrier layer is provided on the other side, and a low-priced metal oxide material is used to block the diffusion of hydrogen ions and capture excess electrons.
Effectively reduce the corrosion of acidic substances on the functional layer, maintain the stability of the properties of the functional layer, and improve its performance.
Smart Images

Figure CN119486480A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite film, a photoelectric device, a preparation method thereof, and a display device. Background Art
[0002] With the development of optoelectronic devices, the properties and functions of composite films prepared from multilayer materials have attracted more and more attention.
[0003] Especially as the application of functional materials becomes more and more extensive, corrosion will occur between adjacent functional material layers due to differences in material properties, which is not conducive to the stable operation of single-functional films and thus affects the performance of functional films. Summary of the invention
[0004] Based on this, the present application provides a composite film, an optoelectronic device, a method for preparing the same, and a display device to improve the performance of the functional film.
[0005] In a first aspect, a composite film is provided, comprising:
[0006] A first functional layer, and an acid-resistant modification layer disposed on one side of the first functional layer, and / or an electron blocking layer disposed on the other side of the first functional layer;
[0007] Wherein, the material of the acid-resistant modification layer is alkaline carbon nanomaterial; and / or the material of the electron blocking layer includes: low-valent metal oxide material.
[0008] Optionally, the surface of the alkaline carbon nanomaterial is connected with hydroxyl groups;
[0009] The alkaline carbon nanomaterial includes: one or more of alkaline graphene oxide, alkaline carbon fiber, alkaline carbon nanotube, alkaline graphene and alkaline graphite;
[0010] and / or,
[0011] The low-valent metal oxide material includes one or more of Cu2O, SnO, NiO, FeO, CoO, WO2 and MoO2;
[0012] and / or,
[0013] The thickness of the acid-resistant modified layer is 10 to 20 nm;
[0014] and / or,
[0015] The thickness of the electron blocking layer is 5 to 10 nm;
[0016] and / or,
[0017] The material of the first functional layer includes: one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, a transition metal oxide and a first transition metal sulfide compound, wherein the transition metal oxide is selected from one or more of NiO, MoO3, WO3 and CuO, and the first transition metal sulfide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS;
[0018] and / or,
[0019] The thickness of the first functional layer is 30-150 nm.
[0020] In a second aspect, a photoelectric device is provided, comprising: an anode, a composite film as described in the first aspect, and a cathode stacked in sequence;
[0021] Wherein, the acid-resistant modification layer is arranged close to the anode, and the electron blocking layer is arranged close to the cathode.
[0022] Optionally, the optoelectronic device further comprises a light-emitting layer;
[0023] The thickness of the light-emitting layer is 10 to 60 nm;
[0024] And / or, the material of the anode and / or the cathode includes one or more of a metal, a carbon material and a metal oxide; the metal of the anode and / or the cathode includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; and / or, the carbon material of the anode and / or the cathode includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; and / or, the metal oxide of the anode and / or the cathode includes a doped or undoped metal oxide, including ITO, FTO, ATO, One or more of AZO, GZO, IZO, MZO and AMO, or a composite electrode comprising a metal sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode comprises one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2;
[0025] And / or, the material of the light-emitting layer includes: an organic light-emitting material and / or a quantum dot light-emitting material; the organic light-emitting material includes: at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-10-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;And / or, the quantum dot luminescent material comprises: at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe , CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPb At least one of SSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInN As, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or, the core of the quantum dot of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dot of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots. ;
[0026] Optionally, the optoelectronic device further comprises: a hole injection layer;
[0027] The hole injection layer is arranged between the acid-resistant modification layer and the anode.
[0028] Optionally, the material of the hole injection layer includes: one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, copper phthalocyanine and a second transition metal sulfur compound, and the second transition metal sulfur compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS;
[0029] and / or,
[0030] The thickness of the hole injection layer is 30-40 nm.
[0031] Optionally, the optoelectronic device further comprises an electron transport layer and / or an electron injection layer; the material of the electron transport layer and / or the electron injection layer comprises an inorganic material and / or an organic material;
[0032] The inorganic material of the electron transport layer and / or the electron injection layer is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; and / or, the organic material of the electron transport layer and / or the electron injection layer is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.
[0033] In a third aspect, a method for preparing a photoelectric device is provided, comprising:
[0034] Providing an anode, on which an acid-resistant modification layer, a first functional layer, an electron blocking layer and a cathode are sequentially arranged; or,
[0035] Providing a cathode, on which an electron blocking layer, a first functional layer, an acid-resistant modification layer and an anode are sequentially arranged;
[0036] Wherein, the preparation of the acid-resistant modified layer comprises: depositing alkaline carbon nanomaterials to form an acid-resistant modified layer;
[0037] The preparation of the electron blocking layer comprises: depositing a low-valent metal oxide material to form the electron blocking layer.
[0038] Optionally, the preparation of the acid-resistant modified layer includes: depositing alkaline carbon nanomaterials to form the acid-resistant modified layer, comprising:
[0039] Providing a basic carbon nanomaterial and a first solvent;
[0040] Mixing the alkaline carbon nanomaterial and the first solvent to obtain a mixed solution;
[0041] Adding alkali to the mixed solution, adjusting the pH value of the mixed solution to 8-8.6, and preparing an alkaline dispersed solution of the alkaline carbon nanomaterial;
[0042] Using a solution method, laying the alkaline dispersed solution on the anode or the first functional layer to form the acid-resistant modification layer;
[0043] Optionally, the preparation of the electron blocking layer comprises: depositing a low-valent metal oxide material to form the electron blocking layer, comprising:
[0044] Preparation of low-valent metal oxide nanoparticles;
[0045] Mixing low-valent metal oxide nanoparticles with a second solvent to prepare a dispersed solution of the low-valent metal oxide nanoparticles;
[0046] The electron blocking layer is prepared by laying a dispersed solution containing the low-valent metal oxide nanoparticles on the first functional layer or the cathode.
[0047] In a fourth aspect, a display device is provided, comprising:
[0048] The optoelectronic device as described in the second aspect, or the optoelectronic device prepared by the method as described in the third aspect.
[0049] Compared with the prior art, this application has the following beneficial effects:
[0050] By setting an acid-resistant modification layer on one side of the first functional layer, the material of the acid-resistant modification layer is an alkaline carbon nanomaterial. The alkaline carbon nanomaterial in the acid-resistant modification layer can combine with hydrogen ions in external acidic substances, thereby blocking the diffusion of hydrogen ions into the first functional layer and reducing the corrosion of the first functional layer caused by acidic substances; in this way, the stability of the properties of the first functional layer itself can be ensured, thereby improving the performance of the first functional layer.
[0051] By providing an electron blocking layer on the other side of the first functional layer, the electron blocking layer can be used to capture excess electrons, thereby preventing the excess electrons from undergoing redox reactions with the material of the first functional layer and thereby destroying the first functional layer, thereby maintaining the material and performance stability of the first functional layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 A schematic diagram of a cross-sectional structure of a composite film provided in an embodiment of the present application;
[0053] Figure 2 A schematic cross-sectional view of a photoelectric device provided in an embodiment of the present application;
[0054] Figure 3 A schematic cross-sectional structure diagram of another optoelectronic device provided in an embodiment of the present application. DETAILED DESCRIPTION
[0055] The present application is further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the present application disclosure more thorough and comprehensive.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0057] Based on the above technical problems, some embodiments of the present application provide a composite film 10, such as Figure 1 As shown, it includes: a first functional layer 1, and an acid-resistant modification layer 2 arranged on one side of the first functional layer 1, and / or, an electron blocking layer 3 arranged on the other side of the first functional layer 1. The material of the acid-resistant modification layer 2 is an alkaline carbon nanomaterial; and / or, the material of the electron blocking layer 3 includes: a low-valent metal oxide material.
[0058] The carbon nanomaterial may have good carrier transport properties, and the alkaline carbon nanomaterial may make the carbon nanomaterial alkaline, thereby neutralizing the acidic substances.
[0059] Low-valent metal oxides refer to metal oxides whose valence in the oxide is not the highest, and can also be called metal suboxides. Compared with "normal" oxides, the number of element atoms with low electronegativity is relatively large. For example, the highest valence of copper is +2, so the Cu in Cu2O is +1, and in this case, Cu2O is a low-valent metal oxide.
[0060] This type of metal oxide material is a type of metal oxide that uses holes as carriers to conduct charge. The structural defects of this material itself are metal ion vacancies. There are defect states of different depths at the bottom energy level of the conduction band, which can capture excess electrons.
[0061] In some embodiments, the material of the first functional layer 1 may include: TFB (Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-butylphenyl)], Poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-dioctylfluorenyl-2,7-diyl)]) and the like.
[0062] Here, it should be noted that before the acid-resistant modification layer 2 and / or the electron blocking layer 3 are provided, the first functional layer 1 can, for example, be in direct contact with the hole injection layer 4. At this time, if the material of the hole injection layer 4 includes acidic substances such as polyethylenedioxythiophene / polystyrenesulfonate (Poly(3,4-ethylenedioxythiophene) / poly(styrenesulfonate), PEDOT:PSS) materials, the hole transport material will be corroded during the long-term use of the device, thereby resulting in a decrease in the luminous efficiency and life of the device. In addition, when the ability and stability of the first functional layer 1 are poor, resulting in an unbalanced carrier injection of the entire optoelectronic device, excess electrons will gather at the interface of the first functional layer 1, and then undergo an oxidation-reduction reaction with it, further reducing the device life.
[0063] In the composite film 10 provided in the embodiment of the present application, an acid-resistant modification layer 2 is provided on one side of the first functional layer 1, and the material of the acid-resistant modification layer 2 is an alkaline carbon nanomaterial. Therefore, when the functional layer adjacent to the first functional layer 1 contains an acidic substance such as PEDOT:PSS, the alkaline carbon nanomaterial in the acid-resistant modification layer 2 can combine with the hydrogen ions in the acidic substance, thereby blocking the diffusion of hydrogen ions into the first functional layer 1 and reducing the corrosion of the first functional layer 1 by the acidic substance; in this way, the stability of the properties of the first functional layer 1 itself can be ensured, thereby improving the performance of the first functional layer 1.
[0064] By providing an electron blocking layer 3 on the other side of the first functional layer 1, the electron blocking layer 3 can be used to capture excess electrons, thereby preventing the excess electrons from undergoing redox reactions with the material of the first functional layer 1 and thereby destroying the first functional layer 1, thereby maintaining the material and performance stability of the first functional layer 1.
[0065] In some embodiments, the surface of the alkaline carbon nanomaterial is connected with hydroxyl groups; the alkaline carbon nanomaterial includes: one or more of alkaline graphene oxide, alkaline carbon fiber, alkaline carbon nanotube, alkaline graphene and alkaline graphite; and / or, the low-valent metal oxide material includes: one or more of Cu2O, SnO, NiO, FeO, CoO, WO2 and MoO2; optionally, the low-valent metal oxide material is Cu2O; and / or, the material of the first functional layer 1 may include: poly (3,4-ethylenedioxythiophene) -polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-difluoroethane; One or more of methane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, a transition metal oxide and a first transition metal sulfide compound, the transition metal oxide is selected from one or more of NiO, MoO3, WO3 and CuO, the first transition metal sulfide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS; and / or, the thickness of the first functional layer 1 is 30 to 150 nm; and / or, the thickness of the acid-resistant modification layer 2 is 10 to 20 nm; and / or, the thickness of the electron blocking layer 3 is 5 to 10 nm.
[0066] The surface of the acid-resistant modified layer 2 has hydroxyl functional groups, which are exposed and can directly combine with hydrogen ions, thereby reducing the corrosion of hydrogen ions into the first functional layer 1 .
[0067] Among them, graphene oxide is the oxide of graphene, generally represented by GO. After oxidation, the number of oxygen-containing functional groups on it increases, making its properties more active than graphene. Carbon nanotubes are a one-dimensional quantum material with a special structure (radial size is nanometers, axial size is micrometers, and both ends of the tube are basically sealed). Graphene is a sp 2 A new material with a single-layer two-dimensional honeycomb lattice structure in which hybrid-connected carbon atoms are tightly packed. In addition to the honeycomb layered structure in which σ bonds link other carbon atoms to form hexagonal rings, the pz orbital of each carbon atom perpendicular to the layer plane can form a large multi-atom π bond that runs through the entire layer, thus having excellent electrical and optical properties. Graphite is a transitional crystal between atomic crystals, metal crystals, and molecular crystals. In the crystal, carbon atoms in the same layer are connected by sp 2Hybridization forms covalent bonds, each carbon atom is connected to three other carbon atoms, and six carbon atoms form a regular hexagonal ring on the same plane, stretching to form a layered structure; each carbon atom on the same plane has one p orbital left, which overlaps each other to form a delocalized π bond. Electrons can move freely in the lattice and can be excited. Therefore, graphite has a metallic luster and can conduct electricity and heat. Carbon fiber (CF for short) is a new type of fiber material with a carbon content of more than 95% and high strength and high modulus.
[0068] These materials all have good carrier transport properties, for example, can be used to transport holes.
[0069] In some optional embodiments, the alkaline carbon nanomaterial includes alkaline graphene oxide. Graphene oxide is flaky and can maximize the carrier transport performance by utilizing its high π-π conjugation degree and good carrier transport capability.
[0070] In addition, through the hydroxyl functional groups, a good cross-linking network can be established between graphene oxide layers, thereby further improving the carrier transmission path and transmission efficiency.
[0071] Some embodiments of the present application provide an optoelectronic device 100, such as Figure 2 and Figure 3 As shown, it includes: a stacked anode 20, a composite film 10 as described above, and a cathode 40;
[0072] The acid-resistant modified layer 2 is disposed close to the anode 20 , and the electron blocking layer 3 is disposed close to the cathode 40 .
[0073] Here, there are two structures. The first structure is as follows: Figure 2 As shown, the anode 20, the composite film 10 and the cathode 40 are arranged in order from bottom to top; the second structure, as shown in Figure 3 As shown, the anode 20, the composite film 10 and the cathode 40 are arranged in sequence from top to bottom.
[0074] In some embodiments, Figure 2 and Figure 3 As shown, the optoelectronic device further includes a light-emitting layer 30, which is disposed between the composite film 10 and the cathode 40, and the thickness of the light-emitting layer 30 is 10 to 60 nm;
[0075] and / or,
[0076] The material of the anode 20 and / or the cathode 40 includes one or more of a metal, a carbon material and a metal oxide; the metal of the anode 20 and / or the cathode 40 includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; and / or, the carbon material of the anode 20 and / or the cathode 40 includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; and / or, the metal oxide of the anode 20 and / or the cathode 40 includes a doped or undoped metal oxide, including ITO (Indium Tin Oxide), FTO (F-doped Tin Oxide), ATO (Antimony Doped Tin Oxide), AZO (Al-doped Zinc Oxide), GZO (Gallium doped Zinc Oxide), IZO (Indium-Zinc-Oxide), MZO (Mg-doped One or more of ZincOxide (Mg-doped zinc oxide) and AMO (Active Magnesium Oxide), or a composite electrode comprising a metal sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode comprises one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2;
[0077] and / or,
[0078] The material of the light-emitting layer 30 includes: an organic light-emitting material and / or a quantum dot light-emitting material; the organic light-emitting material includes: at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-10-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;And / or, the quantum dot luminescent material includes: at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe , CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnP bSSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaI At least one of nNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or, the core of the quantum dot of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dot of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots. ;
[0079] Alternatively, if Figure 2 and Figure 3As shown, the photoelectric device 100 further includes: a hole injection layer 70 , and the hole injection layer 70 is disposed between the acid-resistant modification layer 2 and the anode 20 .
[0080] In some embodiments, the material of the hole injection layer 70 includes: one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, copper phthalocyanine, and a second transition metal sulfur compound, wherein the second transition metal sulfur compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS; and / or, the thickness of the hole injection layer 70 is 30 to 40 nm.
[0081] In some embodiments, Figure 2 and Figure 3 As shown, the optoelectronic device 100 further includes an electron transport layer 50 and / or an electron injection layer 60; the material of the electron transport layer 50 and / or the electron injection layer 60 includes an inorganic material and / or an organic material;
[0082] Optionally, and / or,
[0083] The inorganic material of the electron transport layer 50 and / or the electron injection layer 60 is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; and / or, the organic material of the electron transport layer and / or the electron injection layer is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.
[0084] Some embodiments of the present application provide a method for preparing a photoelectric device, comprising:
[0085] Providing an anode, and sequentially arranging an acid-resistant modification layer, a first functional layer, an electron blocking layer and a cathode on the anode; or,
[0086] Providing a cathode, and sequentially arranging an electron blocking layer, a first functional layer, an acid-resistant modification layer and an anode on the cathode;
[0087] The preparation of the acid-resistant modified layer includes: depositing alkaline carbon nanomaterials to form an acid-resistant modified layer;
[0088] The preparation of the electron blocking layer includes: depositing a low-valent metal oxide material to form the electron blocking layer.
[0089] In some embodiments, the preparation of the acid-resistant modified layer includes: depositing alkaline carbon nanomaterials to form the acid-resistant modified layer, including:
[0090] Providing a basic carbon nanomaterial and a first solvent;
[0091] Mixing an alkaline carbon nanomaterial and a first solvent to obtain a mixed solution;
[0092] Adding alkali to the mixed solution to adjust the pH value of the mixed solution to 8-8.6 to prepare an alkaline dispersed solution of alkaline carbon nanomaterials;
[0093] The alkaline dispersion solution is laid on the anode or the first functional layer to form the acid-resistant modification layer.
[0094] In some embodiments, the method of laying the alkaline dispersion solution on the anode or the first functional layer may include any one of drop coating, spray coating, blade coating, spin coating, inkjet printing and screen printing.
[0095] In some embodiments, the preparation of the electron blocking layer includes: depositing a low-valent metal oxide material to form the electron blocking layer, including:
[0096] Prepare low-valent metal oxide nanoparticles, optionally, the particle size of the low-valent metal oxide nanoparticles is 5 to 10 nm;
[0097] mixing low-valent metal oxide nanoparticles with a second solvent to prepare a dispersed solution of low-valent metal oxide nanoparticles;
[0098] The dispersed solution containing the low-valent metal oxide nanoparticles is laid on the first functional layer or the cathode to prepare an electron blocking layer.
[0099] In some embodiments, the dispersion solution may be applied on the first functional layer or the cathode in a manner including any one of drop coating, spray coating, blade coating, spin coating, inkjet printing, and screen printing.
[0100] Some embodiments of the present application provide a display device, including the optoelectronic device as described above, or an optoelectronic device prepared by the method as described above.
[0101] Examples of the display device may be a television, a computer, or an ATM machine.
[0102] In the following examples and comparative examples, all raw materials can be purchased in commercial form, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are processed in the same way.
[0103] Composite film embodiment 1
[0104] Example 1 provides a composite film, which includes an acid-resistant modification layer (with a thickness of 20 nm), a first functional layer (with a thickness of 30 nm) and an electron blocking layer (with a thickness of 10 nm).
[0105] The preparation method of the composite film is as follows:
[0106] Step 1), prepare a basic graphene oxide layer, and the preparation method is as follows:
[0107] 50 ml of concentrated sulfuric acid and 30 ml of concentrated nitric acid were mixed evenly in a 5°C water bath, 3 g of graphite was added and stirred for 30 min to fully dissolve, and then 33 g of potassium chlorate powder was added, and then the ice-water bath was stopped, and the reaction was carried out at room temperature for 96 h, and then the mixed solution was poured into 1000 ml of deionized water to obtain a graphene oxide dispersion, the graphene oxide was diluted to 1 mg / ml, and then 130 μl of 0.2 mol / Ld NaOH was added to 10 ml of the graphene oxide dispersion, and the pH was controlled at 8 to obtain an alkaline graphene oxide nanosheet dispersion, and then 10 drops of it were inkjet printed into a 20 nm thick film, which was covered on the surface of the ITO substrate;
[0108] Step 2), using a spin coating method to prepare a 30nm first functional layer (material is TFB) on the alkaline graphene oxide nanosheet film;
[0109] Step 3), prepare a cuprous oxide film on the surface of the first functional layer, the preparation method is as follows:
[0110] 0.7 mol / L trisodium citrate and 1.2 mol / L sodium carbonate were mixed evenly, and then mixed with 0.68 mol / L copper sulfate, and 0.5 mol / L reducing agent glucose was added to the mixture, and the mixture was reacted in an 80°C water bath for 15 minutes. Cuprous oxide nanoparticles with a diameter of 10 nm were obtained by centrifugation, and then dissolved in ethanol solvent and printed on the surface of the first functional layer to prepare a 10 nm thin film as an electron blocking layer; thus, a composite thin film was obtained.
[0111] Composite film embodiment 2
[0112] The preparation method of the composite film provided in Example 2 is basically the same as that of the composite film provided in Example 1, with the only difference being that: in step 1), the material of the composite film is alkaline carbon fiber, the pH is controlled at 8.6, and its alkaline dispersion 10 is sprayed on the surface of the ITO substrate to form a film with a thickness of 20 nm; in step 3), the thickness of the electron blocking layer is 7 nm.
[0113] Composite film embodiment 3
[0114] The preparation method of the composite film provided in Example 3 is basically the same as that of the composite film provided in Example 1, with the only difference being that in step 1), the material of the composite film is alkaline carbon nanotubes, the pH of the alkaline dispersion is controlled at 8.4, and the alkaline dispersion is spin-coated on the surface of the ITO substrate to form a film with a thickness of 20 nm.
[0115] Composite film embodiment 4
[0116] The preparation method of the composite film provided in Example 4 is basically the same as that of the composite film provided in Example 1, with the only difference being that in step 1), the material of the composite film is alkaline graphite, the pH of the alkaline dispersion is controlled at 8.0, and the alkaline dispersion is scraped onto the surface of the ITO substrate to form a film with a thickness of 20 nm.
[0117] Photoelectric device embodiment 5
[0118] Example 5 provides a light-emitting device. It includes a substrate, a QLED (Quantum DotLight Emitting Diodes) optoelectronic device bonded to the substrate, and an encapsulation film for encapsulating the QLED optoelectronic device. The light-emitting device includes, from bottom to top: an ITO substrate, a hole injection layer (40 nm thick), a composite film as described in Example 1 (including: an acid-resistant modification layer (20 nm thick), a first functional layer (30 nm thick) and an electron blocking layer (10 nm thick)), a red quantum dot light-emitting layer (30 nm thick), an electron transport layer (30 nm thick), a second electrode (70 nm thick), and an encapsulation cover. The light-emitting device of this embodiment is prepared as follows:
[0119] Step 01), prepare a hole injection layer (material is PEDOT:PSS) on the ITO substrate, with a thickness of about 40nm;
[0120] Step 02), preparing an acid-resistant modification layer, a first functional layer and an electron blocking layer on the hole injection layer. The specific preparation method can refer to Example 1;
[0121] Step 03), a red QD (Quantum Dot) functional layer and a zinc oxide functional layer are sequentially formed on Cu2O.
[0122] Step 04) Prepare a 70nm thick silver electrode by evaporating silver and package it with a cover plate.
[0123] Photoelectric device embodiment 6
[0124] The structure of the light-emitting device provided in Example 6 is substantially the same as that of the light-emitting device provided in Example 5, except that the composite film in Example 6 is the composite film provided in Example 2.
[0125] Photoelectric device embodiment 7
[0126] The structure of the light-emitting device provided in Example 7 is substantially the same as that of the light-emitting device provided in Example 5, except that the composite film in Example 7 is the composite film provided in Example 3.
[0127] Photoelectric device embodiment 8
[0128] The structure of the light-emitting device provided in Example 8 is substantially the same as that of the light-emitting device provided in Example 5, except that the composite film in Example 8 is the composite film provided in Example 4.
[0129] Photoelectric device embodiment 9
[0130] The structure of the light-emitting device provided in Example 9 is basically the same as that of the light-emitting device provided in Example 5, except that when preparing the composite film, the thickness of the electron blocking layer is 5 nm, and the light-emitting layer is a blue quantum dot light-emitting layer with a thickness of 30 nm.
[0131] Photoelectric device embodiment 10
[0132] The light-emitting device provided in Example 10 has substantially the same structure as the light-emitting device provided in Example 5, except that when preparing the composite film, the thickness of the alkaline graphene oxide layer is 10 nm.
[0133] Photoelectric device embodiment 11
[0134] The structure of the light-emitting device provided in Example 11 is substantially the same as that of the light-emitting device provided in Example 5, except that when preparing the composite film, the thickness of the alkaline graphene oxide layer is 15 nm, and the material of the electron blocking layer is Fe2O3 with a thickness of 8 nm. In the preparation method, the preparation method of Fe2O3 is:
[0135] 0.7 mol / L trisodium citrate and 1.2 mol / L sodium carbonate were mixed evenly, and then mixed with 0.72 mol / L ferric sulfate. 0.66 mol / L reducing agent glucose was added to the mixture, and the mixture was reacted in a 90°C water bath for 18 minutes. Iron oxide nanoparticles with a diameter of 8 nm were obtained by centrifugal separation.
[0136] Photoelectric device embodiment 12
[0137] The light-emitting device provided in Example 12 is different from the light-emitting device provided in Example 5 in that no electron blocking layer is provided.
[0138] Photoelectric device embodiment 13
[0139] The light-emitting device provided in Example 13 is different from the light-emitting device provided in Example 5 in that no acid-resistant modification layer is provided.
[0140] Photoelectric device comparative example 1
[0141] The light-emitting device provided in Comparative Example 1 is basically the same as the light-emitting device provided in Example 5, except that: the device structure of Comparative Example 1 includes, from bottom to top, an ITO substrate, a hole injection layer (thickness of 40 nm), a first functional layer (thickness of 30 nm), a red quantum dot light-emitting layer (thickness of 30 nm), an electron transport layer (thickness of 30 nm), a second electrode (thickness of 70 nm) and a packaging cover.
[0142] Photoelectric device comparative example 2
[0143] The light-emitting device provided in Comparative Example 2 is basically the same as the light-emitting device provided in Example 5, except that: the device structure of Comparative Example 2 includes, from bottom to top, an ITO substrate, a hole injection layer (40 nm thick), a first functional layer (made of cuprous oxide, 40 nm thick), a red quantum dot light-emitting layer (30 nm thick), an electron transport layer (30 nm thick), a second electrode (70 nm thick) and a packaging cover.
[0144] The luminous performance tests of the light-emitting devices of the above embodiments and comparative examples are shown in Table 1 below:
[0145] Table 1
[0146] Part Number EQE LT95@1000nit(h) Example 5 15.6% 15500 Example 6 14.8% 15800 Example 7 13.5% 14400 Example 8 12.7% 13100 Example 9 6.2% 350 Example 10 15.4% 12200 Embodiment 11 14.3% 11350 Example 12 12.8% 8000 Example 13 13.3% 10300 Comparative Example 1 11.4% 6660 Comparative Example 2 7.3% 2230
[0147] EQE (External Quantum Efficiency) is the ratio of device excitons converted to photons, and is usually used to characterize the efficiency of a device. The higher the EQE, the higher the device efficiency. Since Example 9 is a blue quantum dot device, the efficiency and life of the blue quantum dot device itself are relatively low. LT95@1000Nit refers to the time required for the device to decay to a brightness of 950Nit at an initial brightness of 1000nit.
[0148] It can be seen from Table 1 that by setting an acid-resistant modification layer on the side of the first functional layer close to the hole injection layer, the efficiency and life of the optoelectronic device can be greatly improved compared with not setting the acid-resistant modification layer. By setting an electron blocking layer on the side of the first functional layer close to the quantum dot luminescent material layer, the efficiency and life of the optoelectronic device can be better improved compared with not setting the electron blocking layer. By setting an acid-resistant modification layer on the side of the first functional layer close to the hole injection layer and setting an electron blocking layer on the side of the first functional layer close to the quantum dot luminescent material layer, the efficiency and life of the optoelectronic device can be further improved. At the same time, by setting the material of the first functional layer to metal oxide in Comparative Example 2, the efficiency and life of the optoelectronic device are greatly reduced, indicating that when the material of the first functional layer is TFB, the optoelectronic device has a higher efficiency and life. By setting an acid-resistant modification layer and / or an electron blocking layer, the efficiency and life of the optoelectronic device can be greatly maintained or even increased.
[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0150] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A composite film, characterized in that: include: A first functional layer, and an acid-resistant modification layer disposed on one side of the first functional layer, and / or an electron blocking layer disposed on the other side of the first functional layer; Wherein, the material of the acid-resistant modification layer includes alkaline carbon nanomaterials; and / or the material of the electron blocking layer includes low-valent metal oxide materials.
2. The composite film according to claim 1, characterized in that The surface of the alkaline carbon nanomaterial is connected with hydroxyl groups; The alkaline carbon nanomaterial includes: one or more of alkaline graphene oxide, alkaline carbon fiber, alkaline carbon nanotube, alkaline graphene and alkaline graphite; and / or, The low-valent metal oxide material includes one or more of Cu2O, SnO, NiO, FeO, CoO, WO2 and MoO2; and / or, The thickness of the acid-resistant modified layer is 10 to 20 nm; and / or, The thickness of the electron blocking layer is 5 to 10 nm; and / or, The material of the first functional layer includes: one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, a transition metal oxide and a first transition metal sulfide compound, wherein the transition metal oxide is selected from one or more of NiO, MoO3, WO3 and CuO, and the first transition metal sulfide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS; and / or, The thickness of the first functional layer is 30-150 nm.
3. A photoelectric device, characterized in that: include: A stacked anode, a composite film as claimed in any one of claims 1 to 2, and a cathode; Wherein, the acid-resistant modification layer is arranged close to the anode, and the electron blocking layer is arranged close to the cathode.
4. The optoelectronic device according to claim 3, characterized in that: The optoelectronic device further comprises a light-emitting layer; The thickness of the light-emitting layer is 10 to 60 nm; and / or, The material of the anode and / or the cathode includes one or more of a metal, a carbon material and a metal oxide; the metal of the anode and / or the cathode includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; and / or the carbon material of the anode and / or the cathode includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; and / or the metal oxide of the anode and / or the cathode includes doped or undoped metal oxides, including ITO, FTO, ATO, AZ O, GZO, IZO, MZO and AMO, or a composite electrode comprising a metal sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode comprises one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or, The material of the light-emitting layer includes: organic light-emitting materials and / or quantum dot light-emitting materials; the organic light-emitting materials include: 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-10-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;And / or, the quantum dot luminescent material comprises: at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe , CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPb At least one of SSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInN As, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or, the core of the quantum dot of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dot of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots. ; 5. The optoelectronic device according to claim 3, characterized in that: Also includes: a hole injection layer; The hole injection layer is arranged between the acid-resistant modification layer and the anode.
6. The optoelectronic device according to claim 5, characterized in that: The material of the hole injection layer includes: one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, copper phthalocyanine and a second transition metal sulfur compound, wherein the second transition metal sulfur compound is selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS; and / or, The thickness of the hole injection layer is 30-40 nm.
7. The optoelectronic device according to claim 3, characterized in that: The optoelectronic device further comprises an electron transport layer and / or an electron injection layer, and the materials of the electron transport layer and / or the electron injection layer comprise inorganic materials and / or organic materials; The inorganic material of the electron transport layer and / or the electron injection layer is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; and / or, the organic material of the electron transport layer and / or the electron injection layer is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.
8. A method for preparing a photoelectric device, characterized in that: include: Providing an anode, on which an acid-resistant modification layer, a first functional layer, an electron blocking layer and a cathode are sequentially arranged; or, Providing a cathode, on which an electron blocking layer, a first functional layer, an acid-resistant modification layer and an anode are sequentially arranged; The preparation of the acid-resistant modified layer includes: depositing alkaline carbon nanomaterials to form an acid-resistant modified layer; the preparation of the electron blocking layer includes: depositing low-valent metal oxide materials to form an electron blocking layer.
9. The method according to claim 8, characterized in that The preparation of the acid-resistant modified layer includes: depositing alkaline carbon nanomaterials to form the acid-resistant modified layer, including: Providing a basic carbon nanomaterial and a first solvent; Mixing the alkaline carbon nanomaterial and the first solvent to obtain a mixed solution; Adding alkali to the mixed solution, adjusting the pH value of the mixed solution to 8-8.6, and preparing an alkaline dispersed solution of the alkaline carbon nanomaterial; The alkaline dispersion solution is spread on the anode or the first functional layer to form the acid-resistant modification layer.
10. The method according to claim 8, characterized in that The preparation of the electron blocking layer includes: depositing a low-valent metal oxide material to form the electron blocking layer, including: Providing low-valent metal oxide nanoparticles; Mixing low-valent metal oxide nanoparticles with a second solvent to prepare a dispersed solution of the low-valent metal oxide nanoparticles; The electron blocking layer is prepared by laying a dispersed solution containing the low-valent metal oxide nanoparticles on the first functional layer or the cathode.
11. A display device, characterized in that: include: The optoelectronic device according to any one of claims 3 to 7, or the optoelectronic device prepared by the method according to any one of claims 8 to 10.